Neurovisceral interactions within the brain-heart axis as the basis of neurocardiology - A. S. Limonova; K. N. Germanova; M. V. Gantman; M. A. Nazarova; K. V. Davtyan; P. A. Novikov; A. A. Sukmanova; A. V. Tarasov; M. S. Kharlap; A. I. Ershova; O. M. Drapkina (Кардиоваскулярная терапия и профилактика)
The use of a systematic approach to the study of the etiology of a certain pathology makes it possible to improve the understanding of its pathogenesis, as well as to develop more effective diagnostic and therapeutic approaches, including improving the prediction of its risk. Within this review, we will consider such an area of interdisciplinary research as neurocardiology, which studies the brain-heart axis. Examples of cardiovascular diseases associated with organic and functional disorders of this axis will be considered, as well as the prospects for research in this area and their translational significance for clinical medicine.